Shipping in the north-east Atlantic: Identifying spatial and temporal patterns of change. (June 2022) - Robbins, James R.; Bouchet, Phil J.; Miller, David L.; Evans, Peter G.H.; Waggitt, James; Ford, Alex T.; Marley, Sarah A.
Abstract: Maritime traffic is increasing globally, with a four-fold increase in commercial vessel movements between 1992 and 2012. Vessels contribute to noise and air pollution, provide pathways for non-native species, and collide with marine wildlife. While knowledge of shipping trends and potential environmental impacts exists at both local and global levels, key information on vessel density for regional-scale management is lacking. This study presents the first in-depth spatio-temporal analysis of shipping in the north-east Atlantic region, over three years in a five-year period. Densities increased by 34%, including in 73% of Marine Protected Areas. Western Scotland and the Bay of Biscay experienced the largest increases in vessel density, predominantly from small and slow vessels. Given well-documented impacts that shipping can have on the marine environment, it is crucial that this situation continues to be monitored – particularly in areas designated to protect vulnerable species and ecosystems which may already be under pressure. Graphical abstract: Unlabelled Image Highlights: Shipping densities are increasing in the north-east Atlantic. Densities increased by 34% over five years. Densities increased in 73% of Marine Protected Areas. This has implications for noise exposure, and collision risk to marine wildlife.